A canção caipira de Zé Mulato & Cassiano: representação e lugares retóricos - Tavares, Leonardo Vinicius de Souza (2019)
Our research is located in the area of Portuguese Language, line of research text and discourse, in the oral and written modalities and thematic the study of the social representations and the rhetorical places in four lyrics of songs, of the double caipira Zé Mulato & Cassiano. The problematic involved includes the aspects related to the tensions materialized in the songs, as well as to the work with the social representations and the rhetorical places, in the sense of finding the most adequate means to the treatment of the negative representations crystallized in the society and in the media, about the caipira and the song he produces, aiming at persuasion. Our work is based on the theorists of rhetoric, especially in Aristotle (384-322 a. C. [2011]), Perelman and Olbrechts-Tyteca (1996), Michel Meyer (2007), Ferreira (2010), among others. As for the social representations of the caipira, we chose Moscovici (2015), with the concept of themata, coming from Social Psychology. As for the historical panorama of the caipira, we use scholars such as Dantas (1976), Caldas (1979), Nepomuceno (1999), Cândido (2010), Sant’Anna(2015), among others. The general objective of our research was to analyze, from the perspective of social representations, the themes existing in the lyrics of the double Zé Mulato & Cassiano, and the rhetorical places, more specifically those of the quality, essence and value of the person, that the speaker stands out by means of the epidemic genre to consolidate the caipira ethos and refute, in the rhetorical act, the derogatory representations and caricatures that the common sense attributes to the peasant. Our specific objectives are: a) to analyze, in the lyrics of the songs, how the speaker refutes the negative representations crystallized in society and in the media, about him, using themata; b) to verify how the speaker makes use of the rhetorical places, in order to articulate in the arguments the values, the hierarchies and the beliefs to move the auditorium and to consolidate the ethos of authentic hill country. We conclude that the speaker apodically demonstrates the ability to reflect on dominant values and, using themata, ethos and rhetorical places, re-hierarchizes the values in force in order to rhetorically introduce the values of the social group to wich belongs